Análisis del resultado del índice de desempeño fiscal y causales de la disparidad en dichos resultados en los municipios de Duitama, Paipa, Sogamoso, Nobsa, Tunja y Tuta entre los años 2018 a 2020 (2021)
In the present research, the Fiscal Performance Index in 6 specific municipalities of the department of Boyacá, which are Sogamoso, Nobsa, Duitama, Paipa, Tunja and Tuta in a period of time comprised between the years 2015 to 2020, where, we will analyze the results in terms of the IDF and Statements of Financial Position with reference to the disparity between municipalities and cities in terms of the criteria evaluated by the National Planning Department, it should be noted that the methodology of this research is qualitative with a descriptive approach. Within it, different frameworks will be found, such as the conceptual one, where different concepts will be found to help in the understanding of this research, as well as the theoretical and legal frameworks, where the first will contain information on the IDF and its criteria, and the second will contain the legislation that governs public administration, national development plans and others that are relevant in each municipality. Finally, the results will be presented, which will be obtained from the analysis of the financial situation statements of each municipality by means of graphs and tables, on the other hand, the analysis of the results of the IDF between 2018 and 2020 will be taken into account.